2011
DOI: 10.1021/nn200195k
|View full text |Cite
|
Sign up to set email alerts
|

Nanographene-Constructed Carbon Nanofibers Grown on Graphene Sheets by Chemical Vapor Deposition: High-Performance Anode Materials for Lithium Ion Batteries

Abstract: We report on the fabrication of 3D carbonaceous material composed of 1D carbon nanofibers (CNF) grown on 2D graphene sheets (GNS) via a CVD approach in a fluidized bed reactor. Nanographene-constructed carbon nanofibers contain many cavities, open tips, and graphene platelets with edges exposed, providing more extra space for Li(+) storage. More interestingly, nanochannels consisting of graphene platelets arrange almost perpendicularly to the fiber axis, which is favorable for lithium ion diffusion from differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
215
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 280 publications
(219 citation statements)
references
References 56 publications
3
215
1
Order By: Relevance
“…[ 60 ] Despite previous papers claimed a certain fragility of bare RGO paper electrodes, [ 35 ] these last two research efforts clearly demonstrated that the introduction of defects, or the direct functionalization of RGO's surface with other electroactive species, could enable fl exible graphene-based electrodes. Similarly, other research efforts on N-doped RGO [ 61 ] and RGO paper functionalized with CNT [ 62,63 ] were reported, but no substantial improvement in terms of electrochemical performance could be observed (Table 1 ). Moreover, a chemically activated RGO paper was also tested as LIB anode [ 64 ] but, unfortunately, it showed very poor performance (i.e., 1 st cycle irreversible capacity of about 86% and a lithiation capacity retention of about 16% after 10 cycles at 20 mA g −1 ) ( Table 1 ).…”
Section: Continuedmentioning
confidence: 60%
See 1 more Smart Citation
“…[ 60 ] Despite previous papers claimed a certain fragility of bare RGO paper electrodes, [ 35 ] these last two research efforts clearly demonstrated that the introduction of defects, or the direct functionalization of RGO's surface with other electroactive species, could enable fl exible graphene-based electrodes. Similarly, other research efforts on N-doped RGO [ 61 ] and RGO paper functionalized with CNT [ 62,63 ] were reported, but no substantial improvement in terms of electrochemical performance could be observed (Table 1 ). Moreover, a chemically activated RGO paper was also tested as LIB anode [ 64 ] but, unfortunately, it showed very poor performance (i.e., 1 st cycle irreversible capacity of about 86% and a lithiation capacity retention of about 16% after 10 cycles at 20 mA g −1 ) ( Table 1 ).…”
Section: Continuedmentioning
confidence: 60%
“…In all these cases, however, only modest improvements (especially in terms of cycling stability) were observed with respect to the reports published few years before. Although several publications reported the active material mass loadings, [ 58,60,65,129,130,132,138,142,147,168,172,[177][178][179][180] as well as the tap density of the active material [ 57 ] and the density of the electrode, [ 63 ] no considerations about volumetric capacity were made. Some progression on composite anodes based on graphene and germanium (i.e., alloy material), MFe 2 O 4 (M = Co, Ni, Cu) and M x S y (M = Sn, Sb, In) were reported in 2012.…”
mentioning
confidence: 99%
“…16 Carbon nanofibers were grown by CVD on graphene sheets synthesized by a modified Hummers method; the carbon nanofibers with many cavities, open tips, as well as edges of exposed graphene platelets can be homogeneously distributed between the graphene sheets as spaces to separate the neighboring graphene and be beneficial for fast ion/electron transfer as well as sufficient contact between active materials as well as electrolyte. 17 Vertically aligned CNTs were directly grown by CVD (60 sccm C 2 H 2 , 120 sccm H 2 , 200 sccm Ar, 750°C) on graphene paper coated with Fe as well as Al 2 O 3 and higher as well as more stable discharge capacity compared with graphene paper as well as CNTs was achieved. 18 Graphene films were grown on copper foil by low pressure CVD (20 torr, 1000°C, 100 sccm CH 4 , 200 sccm H 2 , 200 sccm Ar), then functionalized with 1-pyrenebutyric acid by drop casting, and coated with multi-walled carbon nanotubes by drop casting after functionalization.…”
Section: ¹2mentioning
confidence: 99%
“…The interlinked architecture not only shortens transport distances for ions in the well-interconnected wall structure, but also provides a continuous pathway endowing for the fast electron transport. [40] Moreover, the structural interconnectivities guarantee higher electrical conductivity and better mechanical stability. [36,41] Thereby, the design and fabrication of various 3D carbonbased nanostructures, including carbon nanotube networks, graphene gels, graphene foams, and 3D CNFs, have been intensively investigated.…”
mentioning
confidence: 99%